Statistical analysis and inter-comparison of the global solar radiation at two sites in Cyprus. (February 2017) - Kalogirou, S.A.; Pashiardis, S.; Pashiardi, A.
Abstract: A statistical analysis and inter-comparison of the solar global radiation at two sites in Cyprus representing two different climate regimes of the island (Athalassa-inland plain vs Larnaca-coastal location) covering the period November 2012–July 2014 is presented. Mean annual, monthly and daily totals, the diurnal variation, frequency distribution of daily totals at both sites are computed and discussed. The validity of the Liu and Jordan approach to estimate mean hourly global radiation values is confirmed. The same type of statistical analysis was extended to the clearness index and sunshine duration. The results of this analysis are used to characterise and compare the radiation regimes at the two sites. The two sites are characterised by relatively high global and horizontal beam radiation intensities. The annual average daily global radiation intensities exceed the value of 18.5 MJ m −2 at the two sites, whereas the horizontal beam radiation is 11.5 MJ m −2 for Athalassa and 11.9 MJ m −2 for Larnaca, respectively. Consequently, the fraction of the beam component of the global radiation is relatively high at both sites, viz., the annual average daily fraction is > 0.600 at the two sites. Comparing the two sites it seems that Larnaca has slightly higher rates of global radiation than Athalassa, since the average yearly cumulative global irradiation is 6835 MJ m −2 for Athalassa and 7183 MJ m −2 for Larnaca. The annual coefficients of Angstrom formula were estimated using daily clearness index and relative sunshine data. The coefficient values for both stations were close to each other. Highlights: Statistical analysis of global radiation. Monthly and diurnal variation of global radiation. Frequency distribution of global radiation. Relationship between global and other radiation parameters. Comparison of global radiation between two sites.